Developing of EDGIV web application to support voluntary teaching program. Issue 1 (July 2021) - Muhammad, R; Hendriyana, H; Ardimansyah, M I; Furnamasari, Y F
Abstract: The problem of equitable access to quality education in Indonesia is increase seen during the Covid-19. Mataharikecil, as one of the social foundations, is trying to take apart. But based on our observation, not all volunteers know how to teach the students. It can cause the education quality provided does not meet the qualifications set by the government. The purpose of this research is to provide a digital platform that can help volunteer teachers in the learning process, starting from preparation, implementation, to evaluation of the learning process. The platform developed is a web-based application called EDGIV. EDGIV is built using the Framework for Application of System Thinking (FAST) method with the stages consisting of Scope Definition, Problem Analysis, Requirements Analysis, Logic Design, Decision Analysis, Physical Design and Integration, Construction, and Testing, Installation and Delivery. EDGIV provides learning materials features based on the curriculum set by the government, course tracking, and the administration feature. EDGIV uses web technology so volunteer teachers can access EDGIV from any device, anytime, and anywhere. It is hoped that EDGIV can provide guidance for volunteer teachers in providing standardized teaching and make the learning experience enjoyable for teachers and students.